Hemisphere-specific optogenetic stimulation reveals left-right asymmetry of hippocampal plasticity. - Kohl, M; Shipton, O; Deacon, R; Rawlins, J; Deisseroth, K; Paulsen, O (2011)
Postsynaptic spines at CA3-CA1 synapses differ in glutamate receptor composition according to the hemispheric origin of CA3 afferents. To study the functional consequences of this asymmetry, we used optogenetic tools to selectively stimulate axons of CA3 pyramidal cells originating in either left or right mouse hippocampus. We found that left CA3 input produced more long-term potentiation at CA1 synapses than right CA3 input as a result of differential expression of GluN2B subunit-containing NMDA receptors.